Enhancing Scientific Process Skills through Clay-Based Learning Media: An Early Childhood Science Learning Strategy on the Thematic Unit “The Universe” - Nirwana, Nirwana; Amir, Rudi; Sadaruddin, Sadaruddin (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
This study examined the development and implementation of clay-based experimental media to support early childhood science learning on the theme of the universe. Although early science education has received increasing attention, young children often struggle to understand abstract astronomical concepts because they lack access to tangible, developmentally appropriate learning materials. This study addressed this issue through the integration of art-based, hands-on inquiry activities that emphasize sensory exploration as a basis for conceptual understanding. A descriptive qualitative design was conducted in an early childhood education setting in Makassar, Indonesia, involving seventeen informants consisting of two early childhood teachers, ten children aged five to six years, and five parents. Data were collected through classroom observations, semi-structured interviews, and document analysis. The research focused on the process of designing and applying clay-based models of the sun, Earth, moon, and stars to simulate day and night through guided experimentation in a play-based learning environment. The findings indicate that children engaged with concrete representations of astronomical phenomena, demonstrated sustained participation in learning activities, and expressed emerging explanations of light, darkness, and Earth’s rotation. The learning process was also characterized by increased teacher–child interaction during inquiry-oriented discussions. Supporting factors included teacher creativity, the accessibility of low-cost materials, and children’s interest in manipulative activities, while constraining factors involved limited instructional time and variation in teachers’ prior experience with arts-integrated science learning. This study contributes to broader debates on early childhood science education by illustrating how low-cost, tactile learning materials mediate children’s engagement with abstract scientific concepts across early learning contexts in resource-limited educational settings.